Semantic Analysis of Children's Education Curriculum According to the Qur'an: A Study of Q.S. Luqman Verses 12-19 - Jumhur, Jumhur; Wasilah, Wasilah; Nazarmanto, Nazarmanto; Prasetyo, Bambang (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study offers a study of the values ​​of children's education contained in the Qur'an, Surah Luqman, verses 12-19, with the hope that this study can be a reference for educational institutions and the wider community to educate children based on the Qur'an. This study is a library research using the Qur'an as a primary source. The method used is qualitative, and this study uses a language approach and semantic analysis techniques in analyzing data. This study found seven values ​​of children's education contained in the Qur'an, Surah Luqman, verses 12-19, namely gratitude, monotheism, birrul walidaini, piety, establishing prayer, humility, and asceticism. The construction of the seven values ​​into the curriculum content of children's education is as follows: gratitude contains moral values, monotheism contains belief values, birrul walidaini contains social-emotional and moral values, piety contains cognitive values, establishing prayer contains social-emotional values, humility contains moral and social-emotional values, and asceticism contains language and social values. The findings of this study are expected to be a reference for the Muslim community to educate children based on the Qur'an and to be a reference for informal, formal, and non-formal educational institutions in educating children based on the Qur'an.